Capacity of Pneumococci to Activate Macrophage Nuclear Factor κB: Influence on Necroptosis and Pneumonia Severity. (25th March 2017) - Coleman, Fadie T; Blahna, Matthew T; Kamata, Hirofumi; Yamamoto, Kazuko; Zabinski, Mary C; Kramnik, Igor; Wilson, Andrew A; Kotton, Darrell N; Quinton, Lee J; Jones, Matthew R; Pelton, Stephen I; Mizgerd, Joseph P
Abstract: During pneumococcal pneumonia, antibacterial defense requires the orchestrated expression of innate immunity mediators, initiated by alveolar macrophages and dependent on transcription driven by nuclear factor κB (NF-κB). Such immune pressure may select for pneumococci, which avoid or subvert macrophage NF-κB activation. Analyzing pneumococci collected from children in Massachusetts, we found that the activation of macrophage NF-κB by Streptococcus pneumoniae is highly diverse, with a preponderance of low NF-κB activators that associate particularly with complicated pneumonia. Low NF-κB activators cause more severe lung infections in mice, and they drive macrophages toward an alternate and detrimental cell fate of necroptosis. Both outcomes can be reversed by activation of macrophages with pneumococci that are high NF-κB activators. These results suggest that low NF-κB activation is a virulence property of pneumococci and that the appropriate activation of macrophages, including NF-κB, may hold promise as an adjunct therapeutic avenue for pneumococcal pneumonia.